USING AUTODESK INVENTOR PARAMETRIC MODELING IN GLASS SURFACES DESIGN - Nazarko, Olga; Buhaievskyi, Sergiy; Gaponova, Lyudmila (Theory and practice of design, 2025)
The article considers the options for using block glazing in interior decoration and provides a brief historical overview of the popularization of this type of glazing both from the point of view of functional properties and from the point of view of aesthetic perception. Variants of geometric ornamentation are proposed, which are obtained by means of parametric computer modeling, which can be used in the decoration of glass surfaces. Purpose. Application of the capabilities of parametric computer modeling CAD Autodesk Inventor in the design of block interior glazing. Methodology. The research methods consist in reviewing and analyzing modern trends in interior design and applying object-oriented modeling when creating multivariate three-dimensional models. Results. The advantages of using glazing elements in the interior design of premises for various purposes (residential, office, industrial) are considered. A parametric multivariate 3D model of the ornament of a modular glass surface is proposed. Scientific novelty is in the study of a change in the approach to design in the context of digitalization, in particular within the framework of the application of methods related to parametric modeling. Practical relevance is in the use of parameterization in computer modeling to ensure flexibility in changing the design. Thus, by changing several parameters, you can immediately get a new version of the ornament or design in one file of the Autodesk Inventor ipt part environment, in addition, this helps to save time during modeling, reduce material consumption during subsequent production, and speed up work on project visualization.